Isolating Personal Knowledge Spillovers: Coinventor Deaths and Spatial Citation Differentials - Balsmeier, Benjamin; Fleming, Lee; Lück, Sonja (American Economic Review: Insights)
We propose a new method to estimate and isolate the localization of knowledge spillovers due to the physical presence of a person, using after-application but pre-grant deaths of differently located coinventors of the same patent. The approach estimates the differences in local citations between the deceased and still-living inventors at increasingly distant radii. Patents receive 26 percent fewer citations from within a radius of 20 miles around the deceased, relative to still-living coinventors. Differences attenuate with time and distance, are stronger when still-living coinventors live farther from the deceased, and hold for a subsample of possibly premature deaths. (JEL O31, O33, O34, R32)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

A Validation Study for the German Versions of the Feeling Scale and the Felt Arousal Scale for a Progressive Muscle Relaxation Exercise - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Behavioral Sciences)
The aim of the present study is to prove the construct validity of the German versions of the Feeling Scale (FS) and the Felt Arousal Scale (FAS) for a progressive muscle relaxation (PMR) exercise. A total of 228 sport science students conducted the PMR exercise for 45 min and completed the FS, the FAS, and the Self-Assessment Manikin (SAM) in a pre-test–post-test design. A significant decrease in arousal (t(227) = 8.296, p < 0.001) and a significant increase in pleasure (t(227) = 4.748, p < 0.001) were observed. For convergent validity, the correlations between the FS and the subscale SAM-P for the valence dimension (r = 0.67, p < 0.001) and between the FAS and the subscale SAM-A for the arousal dimension (r = 0.31, p < 0.001) were significant. For discriminant validity, the correlations between different constructs (FS and SAM-A, FAS and SAM-P) were not significant, whereas the discriminant analysis between the FS and the FAS revealed a negative significant correlation (r = −0.15, p < 0.001). Together, the pattern of results confirms the use of the German versions of the FS and the FAS to measure the affective response for a PMR exercise.
Keywords: Behavioral Neuroscience; General Psychology; Genetics; Development; Ecology; Evolution; Behavior and Systematics

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

A hybrid multi-attribute decision-making and data envelopment analysis model with heterogeneous attributes: The case of sustainable development goals - Soltanifar, Mehdi; Tavana, Madjid; Santos-Arteaga, Francisco J.; Sharafi, Hamid (Environmental Science & Policy)
Keywords: Management; Monitoring; Policy and Law; Geography; Planning and Development

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Agency: Taking Stock of Workplace Learning Research - Goller, Michael; Paloniemi, Susanna (Research Approaches on Workplace Learning)
This chapter presents a discussion of the concept of agency. Agency is understood as a multifaceted construct describing the idea that human beings make choices, act on these choices, and thereby exercise influence on their own lives as well as their environment. We argue that the concept is discussed from three different perspectives in the literature—transformational, dispositional, and relational—that are each related to learning and development in work contexts. These perspectives do not reflect incompatible positions but rather different aspects of the same phenomena. The chapter also offers an avenue of insight into empirical studies that employ agency as a central concept as well as discussions about concepts that closely overlap with ideas of human beings as agents of power and influence.
Keywords: Agency Workplace learning Professional development Proactivity Self-direction

AI Assisted Interference Classification to Improve EMC Troubleshooting in Electronic System Development - Maalouly, Jad; Hemker, Dennis; Hedayat, Christian; Rückert, Christian; Kaufmann, Ivan; Olbrich, Marcel; Lange, Sven; Mathis, Harald (2022 Kleinheubach Conference)
In this paper, machine learning techniques will be used to classify different PCB layouts given their electromagnetic frequency spectra. These spectra result from a simulated near-field measurement of electric field strengths at different locations. Measured values consist of real and imaginary parts (amplitude and phase) in X, Y and Z directions. Training data was obtained in the time domain by varying transmission line geometries (size, distance and signaling). It was then transformed into the frequency domain and used as deep neural network input. Principal component analysis was applied to reduce the sample dimension. The results show that classifying different designs is possible with high accuracy based on synthetic data. Future work comprises measurements of real, custom-made PCB with varying parameters to adapt the simulation model and also test the neural network. Finally, the trained model could be used to give hints about the error’s cause when overshooting EMC limits.
Keywords: emc; pcb; electronic system development; machine learning; neural network

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Continuous Situation-specific Development of Business Models: Knowledge Provision, Method Composition, Method Enactment - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a continuous challenging activity where different tasks need to be performed, and business decisions need to be made. Both have to fit the constantly changeable situation in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, a method for developing situation-specific business models is needed. As a solution, we refine the concept of situational method engineering (SME) to business model development. SME, in turn, provides means to construct situation-specific development methods out of fragments from a method repository. We develop a concept for the continuous situation-specific development of business models based on design science. The approach uses the roles of a domain expert, a method engineer, and a business developer together with a repository with method fragments for developing business models and a repository with modeling artifacts for supporting the development. Both repositories are filled by utilizing the experience of domain experts. Out of these repositories, situation-specific development methods for developing business models can be continuously composed based on the changeable situation by the method engineer and enacted by the business developer. We implement it as an open-source tool and evaluate its applicability in an industrial case study of developing a business model for a local event platform. Our results show that situation awareness supports the continuous development of business models.
Keywords: Business Model Development; Situational Method Engineering; Situation-specific; Business Model Canvas; Continuous Development

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

A private sustainable partner selection model for green public-private partnerships and regional economic development - Tavana, Madjid; Khalili Nasr, Arash; Mina, Hassan; Michnik, Jerzy (Socio-Economic Planning Sciences)
Keywords: Management Science and Operations Research; Statistics; Probability and Uncertainty; Strategy and Management; Economics and Econometrics; Geography; Planning and Development

A multicriteria-optimization model for cultural heritage renovation projects and public-private partnerships in the hospitality industry - Tavana, Madjid; Azadmanesh, Abdolreza; Nasr, Arash Khalili; Mina, Hassan (Current Issues in Tourism)
Keywords: Tourism; Leisure and Hospitality Management; Geography; Planning and Development

Situation-specific Business Model Development Methods for Mobile App Developers - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Enterprise, Business-Process and Information Systems Modeling)
The development of effective business models is an essential task in highly competitive markets like mobile ecosystems. Existing development methods for these business models do not specifically focus that the development process profoundly depends on the situation (e.g., market size, regulations) of the mobile app developer. Here, a mismatch between method and situation can lead to poor resource management and longer development cycles. In software engineering, situational method engineering is used for software projects to configure a development method out of a method repository based on the project situation. Analogously, we support creating situation-specific business model development methods with a method base and new user roles. Here, the method engineer obtains the knowledge of the domain expert and stores it in the method base as elements, building blocks, and patterns. The expert knowledge is derived from a grey literature review on mobile development processes. After this, the method engineer constructs the development method based on the described situation of the business developer. We provide an open-source tool and evaluate it by constructing a local event platform's business model development method.
Keywords: Business Model Development; Situational Method Engineering; Mobile App; Business Model Development Tools

Towards Visualizing and Simulating Business Models in Dynamic Platform Ecosystems - Vorbohle, Christian; Gottschalk, Sebastian (Proceedings of the 29th European Conference on Information Systems (ECIS))
Platform-based business models underlie the success of many of today’s largest, fastest-growing, and most disruptive companies. Despite the success of prominent examples, such as Uber and Airbnb, creating a profitable platform ecosystem presents a key challenge for many companies across all industries. Although research provides knowledge about platforms’ different value drivers (e.g., network effects), companies that seek to transform their current business model into a platform-based one lack an artifact to reduce knowledge boundaries, collaborate effectively, and cope with the complexities and dynamics of platform ecosystems. We address this challenge by developing two artifacts and combining research from variability modeling, business model dependencies, and system dynamics. This paper presents a design science research approach to develop the platform ecosystem modeling language and the platform ecosystem development tool that support researcher and practitioner by visualizing and simulating platform ecosystems.
Keywords: Platform Ecosystems; Platform Ecosystem Modeling Language; Platform Ecosystem Development Tool; Business Models; Design Science

Situation- and Domain-specific Composition and Enactment of Business Model Development Methods - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Product-focused Software Process Improvement)
Developing effective business models is a complex process for a company where several tasks (e.g., conduct customer interviews) need to be accomplished, and decisions (e.g., advertisement as a revenue stream) must be made. Here, domain experts can guide the choices of tasks and decisions with their knowledge. Nevertheless, this knowledge needs to match the situation of the company (e.g., financial resources) and the application domain of the product/service (e.g., mobile app) to reduce the risk of developing ineffective business models with low market penetration. This is not covered by one-size-fits-all development methods without tailoring before the enaction. Therefore, we conduct a design science study to create a situation-specific development approach for business models. Based on situational method engineering and our previous work in storing knowledge of methods and models in distinct repositories, this paper shows the situation-specific composition and enaction of business model development methods. First, the method engineer composes the development method out of both repositories based on the situational context. Second, the business developer enacts the method and develops the business model. We implement the approach in a tool and evaluate it with a industrial case study on mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Lean Development; Kanban Boards; Canvas Models

Computers and Education – Recognising Opportunities and Managing Challenges - Passey, Don; Brinda, Torsten; Cornu, Bernard; Holvikivi, Jaana; Lewin, Cathy; Magenheim, Johannes; Morel, Raymond; Osorio, Javier; Tatnall, Arthur; Thompson, Barrie; Webb, Mary (Advancing Research in Information and Communication Technology)
Keywords: Educational technologies; Education and technologies; Digital technologies and education; Information technologies; Communication technologies; Educational technologies and research; Educational technologies and pedagogical practices; Educational technologies and policy; Educational management and technologies; Professional development and educational technologies

The Concept of a Digital Twin and Its Potential for Learning Organizations - Berisha-Gawlowski, Angelina; Caruso, Carina; Harteis, Christian (Digital Transformation of Learning Organizations)
The digital transformation of organizations in the industrial sector is primarily driven by the opportunity to increase productivity while simultaneously reducing costs through integration into a cyber-physical system. One way to fully tap the potential of a cyber-physical system is the concept of the digital twin, i.e., the real-time digital representation of machines and resources involved – including human resources. The vision of representing humans by digital twins primarily aims at increasing economic benefits. The digital twin of a human, however, cannot be designed in a similar way to that of a machine. The human digital twin shall rather enable humans to act within the cyber-physical system. It therefore offers humans a power of control and the opportunity to provide feedback. The concept of the digital twin is still in its infancy and raises many questions in particular from an educational perspective. The contribution aims at answering the following questions and refers to the example of team learning: Which and how much data should and may the digital twin contain in order to support humans in their learning? To what extent will humans be able to control and design their own learning? How may skills, experiences, and social interactions of humans be represented in the digital twin; their growth and further development, respectively? With cyber-physical systems transcending corporate, national, and legal boundaries, what learning culture will be the frame of reference for the involved organizations?
Keywords: Digital twin; Learning organization; Change; Team learning; Professional development

V-model based development of cyber-physical systems and cyber-physical production systems - Gräßler, Iris; Wiechel, Dominik; Roesmann, Daniel; Thiele, Henrik (Procedia CIRP)
Challenges of the development of mechatronic systems and corresponding production systems have increased steadily. Changes are primarily due to increased product complexity and the connection to the internet of things and services, enabling Cyber-Physical Systems (CPS) and Cyber-Physical Production Systems (CPPS). Major innovations of the revised VDI guideline 2206 for developing mechatronic systems are systems thinking as a core element and six checkpoints for structuring deliverables along the V-Model. These checkpoints serve for orientation in result progress and thus enable a structured and complete development process. However, tasks and checkpoints of the new guideline focus on the product development itself without integrating the development of related CPPS, enabling optimization simultaneously to system development. Implications are derived by a three-step analysis. The paper at hand contributes fundamental extensions of the checkpoint questions regarding integrated CPPS development. These questions provide methodical support for system developers of CPPS for CPS by enabling the project manager to check the status, schedule further development steps and evaluate the maturity of the whole, integrated development.
Keywords: Cyber-Physical Production System (CPPS); V-Model; Product System Development; Integrated Development; VDI 2206

A Comparative Analysis of Consumption: Evidence from a Cultural Goods Market - Kaimann, Daniel; Cox, Joe (Sustainability)
This study uniquely employs a fuzzy-set qualitative comparative analysis (fsQCA) technique to account for complex relationships in consumption. The fsQCA technique assumes that relationships are based on a set–subset relationship. This assumption is fundamental when decision-makers are affected by information asymmetry and are, thus, required to jointly evaluate the credibility and reliability of a range of external signals. This issue also affects consumers in markets for cultural goods, where the quality of products is not known with certainty in advance of the purchase decision. Our study uses fsQCA to establish the effect of different quality signals on consumption in the US market for video game software. Our results show that reviews from professional critics alongside brand extension and multi-platform release strategies act as signals of product quality and, therefore, lead to high sales performance.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die Frage, wie sich die Weiterentwicklung der Lehre an Hochschulen systematisch verankern lässt, erfährt mit dem Auslaufen von Förderprogrammen wie dem QPL erneute Aufmerksamkeit. Bislang fehlt es an einer kontextspezifischen Theorie, die lehrbezogenen Wandel an Hochschulen analysier- und gestaltbar macht. In jedem Fall sind Change-Konzepte aus dem betriebswirtschaftlichen Bereich nur sehr beschränkt auf Hochschulen übertragbar. Demgegenüber gibt neuere Forschung Hinweise darauf, welche Kernkategorien eine hochschulspezifische Change- Theorie umfassen könnte. Darauf aufbauend schlägt der Beitrag zwei Konzepte als Kernkategorien einer Theorie lehrbezogenen Wandels an Hochschulen vor.
Keywords: educational development; change management; educational innovation

A Knowledge Development Perspective on Literature Reviews: Validation of a New Typology in the IS Field - Schryen, Guido; Wagner, Gerit; Benlian, Alexander; Paré, Guy (Communications of the AIS)
Literature reviews (LRs) play an important role in the development of domain knowledge in all fields. Yet, we observe a lack of insights into the activities with which LRs actually develop knowledge. To address this important gap, we (1) derive knowledge building activities from the extant literature on LRs, (2) suggest a knowledge-based typology of LRs that complements existing typologies, and (3) apply the suggested typology in an empirical study that explores how LRs with different goals and methodologies have contributed to knowledge development. The analysis of 240 LRs published in 40 renowned IS journals between 2000 and 2014 allows us to draw a detailed picture of knowledge development achieved by one of the most important genres in the IS field. An overarching contribution of our work is to unify extant conceptualizations of LRs by clarifying and illustrating how LRs apply different methodologies in a range of knowledge building activities to achieve their goals with respect to theory.
Keywords: Literature review; knowledge development; knowledge building activities; knowledge-based typology; information systems research

„Sie sind doch eine Medienklasse!“ - Caruso, Carina; Reis, Oliver (Österreichische Religionspädagogische Forum)
Ausgehend von Ergebnissen zur Mediennutzung und Ausführungen zur Medienkompetenz fokussiert der Beitrag digitale Praktiken im Religionsunterricht. Zur Analyse der mit der Digitalisierung verbundenen Transformation digitaler Praktiken wird die Akteur-Netzwerk-Theorie dargestellt sowie die Begriffe Digitalisierung und Digitalität definiert. Anhand einer Vignette (dichte Beschreibung) wird der Frage nachgegangen, wie sich Lehrkräfte auf Herausforderungen von Digitalität einlassen (können), inwiefern sie digitale Praktiken eröffnen und inwiefern diese mit traditionellen Praktiken verbunden sind.
Keywords: Digitale Praktiken; Digitalisierung; Medienkompetenz; Professionalisierung; Religionsunterricht / digital practices; digitization; digital literacy; teachers' professional development; religious education

Conceptual Change in the Face of Digitalization - Harteis, Christian; Goller, Michael; Caruso, Carina (Frontiers in Education)
The article discusses the explanatory power of conceptual change for research on workplace learning in digitalized workplaces. Interestingly, research on conceptual change is well-established within the area of science education but widely neglected within the broad area of workplace learning research. Digitalization of work establishes new quality of tasks and tools by integrating workers and machines into digital networks. Hence, conceptual change can be considered a core concept for identifying workers’ successful adaption to digital transformation. Therefore, conceptual change research in the area of workplace learning in digitalized workplaces is highly relevant. The article reflects upon reasons, explores the potential of conceptual change for understanding workplace learning in digitalized workplaces, and illustrates the argumentation by exemplarily referring to digitalized farming. Finally, the article provides suggestions for future research.
Keywords: conceptual change; digitalization; workplace learning; professional development; agriculture

Dual Study Programmes as a Design Challenge: Identifying Areas for Improvement as a Starting Point for Interventions - Mordhorst, Lisa; Gössling, Bernd (EDeR. Educational Design Research)
The proportion of freshmen enrolled in dual study programmes has steadily increased in recent years. From the perspective of potential students, these programmes are highly attractive because they combine types of learning that used to be largely separate at an institutional level: vocational and academic learning. In training-integrated dual study programmes, different institutional contexts, governance regimes, teaching styles and learning environments make bridging these two worlds of learning a challenge for both educators and learners. However, these programmes also allow leeway for didactic innovation, through the cooperation of different types of educational institutions and through new ways of using available didactic methods, and for establishing a new relationship between higher education (HE) and vocational education and training (VET). This paper positions training-integrated dual study programmes as an object of design-based research (DBR). By developing and using an extended model for the pedagogic development of HEIs, “pädagogische Hochschulentwicklung” (Brahm, Jenert, & Euler, 2016a, p. 19; Euler, 2013, p. 360), the paper systematically identifies generic educational problems in these hybrids. Based on a literature review, this paper classifies and explains the design challenges at the level of the learning environment, the study programme and the organisation. The challenges revolve mainly around the cooperation and integration of HE and VET. The paper concludes with an outlook on future DBR projects designing dual studies.
Keywords: Dual study programmes; Design challenges; Pedagogic development of HEIs; Literature review; Study programme development; DBR cycle

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Intertwined Development of Business Model and Product Functions for Mobile Applications: A Twin Peak Feature Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Software Business)
Mobile app stores like Apple's AppStore or Google's PlayStore are highly competitive markets for third-party developers wanting to develop successful applications. During the development process, many developers focus on the multitude of product functions but neglect the business model as an equally important part. As a result, developers often fail to meet customer needs, leading to unnecessary development costs and poor market penetration. This, in turn, raises the question of how we intertwine the business model and product functions during the development process to ensure a better alignment between the two. In this paper, we show this intertwined development by adapting the concept of Twin Peaks to the business model and product functions. Based on feature modeling as an abstraction layer, we introduce the concept of a Business Model Decision Line (BMDL) to structure the business model decisions and their relation to product functions structured in a Software Product Line (SPL). The basis of our feature models is the analysis of top listed applications in the app stores of Apple and Google. To create and modify both models, we provide an incremental feature structuring and iterative feature selection process. This combination of abstraction layer and development process supports third-party developers to build successful applications both from a business and a product perspective.
Keywords: Intertwined Development; Twin Peaks; Feature Model; Business Model; Product Functions

Debugging Static Analysis - Nguyen Quang Do, Lisa; Krüger, Stefan; Hill, Patrick; Ali, Karim; Bodden, Eric (IEEE Transactions on Software Engineering)
Keywords: Debugging; Static analysis; Tools; Computer bugs; Standards; Writing; Encoding; Testing and Debugging; Program analysis; Development tools; Integrated environments; Graphical environments; Usability testing

Drafting a Data Science Curriculum for Secondary Schools - Heinemann, Birte; Opel, Simone; Budde, Lea; Schulte, Carsten; Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Wassong, Thomas (Proceedings of the 18th Koli Calling International Conference on Computing Education Research - Koli Calling '18)
Keywords: Curriculum Development; Data Science; Secondary Sc; acm reference format; big data; curriculum development; data literacy; data science; educa-; interdisciplinary; secondary schools; tion

Corporate governance and sustainable business conduct—Effects of board monitoring effectiveness and stakeholder engagement on corporate sustainability performance and disclosure choices - Manning, Bart; Braam, Geert; Reimsbach, Daniel (Corporate Social Responsibility and Environmental Management)
Abstract This study posits that, in the absence of extensive mandatory regulation and auditing, differences in internal and external corporate governance (CG) mechanisms will explain variations in choices concerning corporate sustainability reporting and the interrelated and underlying corporate sustainability performance (CSP). Specifically, we explore whether board monitoring effectiveness as a major internal CG mechanism and stakeholder engagement as a key external CG mechanism are positively associated with sustainability reporting quality (SRQ), compliance with generally accepted sustainability reporting standards (SRC) and guidelines, and CSP for a sample of Dutch firms that have voluntarily disclosed sustainability reports during the years 2012–2016. In addition to these direct effects, we also investigate the potential indirect effects of the CG mechanisms on SRQ and SRC via CSP and distinguish between nonlagged and lag effects. Using structural equation modeling, our results show that, in the short term, monitoring effectiveness positively affects SRQ and SRC. Stakeholder engagement positively affects SRQ and SRC in the short term and is positively related to SRQ via CSP in the longer term, indicating that active stakeholders, over time, may drive companies toward more sustainable business conduct. Finally, the findings that CSP is positively related to SRQ but negatively related to SRC provide further support for signaling and legitimacy theory, respectively. Companies with superior CSP disclose high‐quality information on CSP to signal the firm's superior sustainability performance, whereas poor performing companies legitimize their inferior CSP by complying with more reporting standards, rather than by directly improving their underlying CSP.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Development

Corporate governance and sustainable business conduct—Effects of board monitoring effectiveness and stakeholder engagement on corporate sustainability performance and disclosure choices - Manning, Bart; Braam, Geert; Reimsbach, Daniel (Corporate Social Responsibility and Environmental Management)
Abstract This study posits that, in the absence of extensive mandatory regulation and auditing, differences in internal and external corporate governance (CG) mechanisms will explain variations in choices concerning corporate sustainability reporting and the interrelated and underlying corporate sustainability performance (CSP). Specifically, we explore whether board monitoring effectiveness as a major internal CG mechanism and stakeholder engagement as a key external CG mechanism are positively associated with sustainability reporting quality (SRQ), compliance with generally accepted sustainability reporting standards (SRC) and guidelines, and CSP for a sample of Dutch firms that have voluntarily disclosed sustainability reports during the years 2012–2016. In addition to these direct effects, we also investigate the potential indirect effects of the CG mechanisms on SRQ and SRC via CSP and distinguish between nonlagged and lag effects. Using structural equation modeling, our results show that, in the short term, monitoring effectiveness positively affects SRQ and SRC. Stakeholder engagement positively affects SRQ and SRC in the short term and is positively related to SRQ via CSP in the longer term, indicating that active stakeholders, over time, may drive companies toward more sustainable business conduct. Finally, the findings that CSP is positively related to SRQ but negatively related to SRC provide further support for signaling and legitimacy theory, respectively. Companies with superior CSP disclose high‐quality information on CSP to signal the firm's superior sustainability performance, whereas poor performing companies legitimize their inferior CSP by complying with more reporting standards, rather than by directly improving their underlying CSP.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Development

Recombinant Service Systems Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Business & Information Systems Engineering)
Although many methods have been proposed for engineering service systems and customer solutions, most of these approaches give little consideration to recombinant service innovation. Recombinant innovation refers to reusing and integrating resources that were previously unconnected. In an age of networked products and data, we can expect that many service innovations will be based on adding, dissociating, and associating existing value propositions by accessing internal and external resources instead of designing them from scratch. The purpose of this paper is to identify if current service engineering approaches account for the mechanisms of recombinant innovation and to design a method for recombinant service systems engineering. In a conceptual analysis of 24 service engineering methods, the study identified that most methods (1) focus on designing value propositions instead of service systems, (2) view service independent of physical goods, (3) are either linear or iterative instead of agile, and (4) do not sufficiently address the mechanisms of recombinant innovation. The paper discusses how these deficiencies can be remedied and designs a revised service systems engineering approach that reorganizes service engineering processes according to four design principles. The method is demonstrated with the recombinant design of a service system for predictive maintenance of agricultural machines.
Keywords: Service engineering; Recombinant innovation; (Product-)service system; Design science research; New service development

Recombinant Service System Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Proceedings der 13. Internationalen Tagung Wirtschaftsinformatik (WI 2017))
Although many methods have been proposed for engineering services and customer solutions, most of these approaches give little consideration to recombinant service innovation. In an age of smart products and smart data, we can, however, expect that many of future service innovations need to be based on adding, transferring, dissociating, and associating existing value propositions. The purpose of this paper is to outline what properties constitute recombinant service innovation and to identify if current service engineering approaches fulfill these properties. Based on a conceptual in-depth analysis of 24 service engineering methods, we identify that most methods focus on designing value propositions instead of service systems, view service independent of physical goods, are linear or iterative, and incompletely address the mechanisms of recombinant innovation. We discuss how these deficiencies can be remedied and propose a first conceptual model of a revised se rvice system engineering approach.
Keywords: Service engineering; recombinant innovation; (product - )service system; literature analysis; new service development

The Multifaceted Nature of Agency and Professional Learning - Paloniemi, Susanna; Goller, Michael (Agency at work: An agentic perspective on professional learning and development)
The present volume has aimed to cover a broad range of approaches to agency at work, exploring its relationship with professional learning and development. Thus, the chapters included in this book have discussed the role of agency in learning and development, considering a variety of working life contexts and applying both conceptual and empirical perspectives. This final chapter provides an overview of both the conceptual approaches and the empirical implementations. We see the perspectives as complementary. From the content of the book, we discern the phenomena as falling on two main dimensions, clustering at opposite ends of these dimensions. Thus, the following contrasts are evidenced: (a) agency understood as a personal capacity, vs. agency as behaviour, and (b) agency as an individual phenomenon, vs. agency as a collective phenomenon. All the chapters emphasise that agency is needed for learning and development. However, they differ in how they view the relationships between the concepts. They also exhibit differences in the empirical decisions taken and the research strategies chosen. In this concluding chapter, we discuss the main similarities and differences emerging from the chapters. We also highlight avenues for future research on agency and its relationship with professional learning.
Keywords: Agency; Workplace learning; Professional development

Accounting quality in private firms during the transition towards international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska (Accounting in Europe)
We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.  Full Article  Figures & data References  Citations Metrics  Reprints & Permissions  PDF Abstract We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.
Keywords: private firms; accounting quality; development of accounting standards; IFRS-like standards; Slovenia

Mathematics-related Competence of Early Childhood Teachers Visiting a Continuous Professional Development Course: An Intervention Study - Bruns, Julia; Eichen, Lars; Gasteiger, Hedwig (Mathematics Teacher Education and Development (MTED))
Recent studies highlight early childhood teachers’ mathematics-related competence. Developing this competence should be a main aspect of early childhood teachers’ education. This is, however, not the case in all countries. Consequently, high-quality professional development courses are needed. Based on research results, we developed a competence-oriented continuous professional development course ("EmMa") and examined the effects of "EmMa" by asking: How does "EmMa" affect the development of early childhood teachers’ i) mathematical content knowledge, ii) mathematical pedagogical content knowledge and iii) beliefs towards mathematics in general? To answer these questions, we conducted a pre-test/post-test study including a control group with 99 in-service early childhood teachers. Results show that the course affected teachers’ mathematical pedagogical content knowledge and static orientation towards mathematics positively. From this we conclude that scaling-up "EmMa" might be a suitable approach to bridge the gap between pre-service education with nearly no mathematics and the challenges of early mathematics education.
Keywords: Beliefs; Competency Based Teacher Education; Control Groups; Early Childhood Education; Faculty Development; Foreign Countries; Inservice Teacher Education; Intervention; Mathematical Aptitude; Mathematics Skills; Pedagogical Content Knowledge; Preschool Teachers; Pretests Posttests; Professional Continuing Education; Statistical Analysis; Teacher Competency Testing

Interventionsstudie zur Entwicklung mathematikbezogener Einstellungen frühpädagogischer Fachpersonen - Eichen, Lars; Bruns, Julia (Frühe Bildung)
Keywords: competency development; early childhood mathematics education; professional development course

Implementing Outcome-Oriented Study Programmes at University: The Challenge of Academic Culture - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
In recent years, the design of study programmes in Higher Education (HE) has been given considerable attention by HE practitioners and researchers. Today, a sound body of concepts and experiences on different realisations of Bologna-conforming study programmes is available. The same, however, does not hold true for questions concerning the processes of implementing and further developing programmes. This paper investigates the challenges related with implementation, particularly at universities. A first aim is to understand the specifics of academic culture and their significance for programme implementation and development. Elaborating on this analysis, a second aim is to outline the role of educational developers in this process, as well as the necessary competencies to perform such a role.
Keywords: Programmentwicklung; Studienprogramme; program development; educational development; academic culture; disciplinary culture

Developing study programs as a continuous task-the role of educational developers - Brahm, Taiga; Zellweger, Franziska; Jenert, Tobias; Thomann, Geri
Abstract Summary: Study programs are currently receiving more attention in Europe. In consequence, it can be observed that the roles of program development and management are professionalized. In the proposed round table, we would like to discuss the role of educational developers to support this professionalization via measures of training and process support in the light of recent developments in Switzerland. Abstract Text: Professionalization of program development as an institutional responsibility In Switzerland, different developments in higher education have led to increased attention to the development and management of the study programs such as the Bologna process, an increasingly competitive environment, the tertiarisation of a number of professions formerly acquired through vocational education. Furthermore, the national qualification framework and in particular accreditation processes require HEI to demonstrate the effectiveness of their activities (e.g., Sursock & Smit, 2010). Many different actors have been involved in development processes on the program level but also within educational development units. However, so far a systematic discourse on key issues regarding the management and development of study programs is missing, not only in German-speaking Europe. The following main question will guide the round table session: How can educational development give vital impulses for program development? Our starting points are two approaches or frameworks from Swiss HEI: a) the definition of competencies for new program professionals at the Zurich University for Teacher Education and b) a process for the strategic development of didactically-aligned study programs at the University of St. Gallen. Framework 1: Competencies for program managers The experiences with a training program for study program managers at the Zurich University for Teacher Education are reported. Over a period of four years, a competency profile has been developed and refined. Insights into the challenges and struggles of this role were gained. Despite diverse job characteristics of program managers (often resulting from an institution-specific history), there is a common set of competencies necessary to successfully cope with organizational complexity such as role competency (Schein, 1992) and lateral leadership (Kühl et al., 2005). Framework 2: Towards a systematic development of study programs The second initiative concerns the strategic approach to program development implemented at the University of St. Gallen (Brahm & Jenert, 2013; Jenert, 2011). In this structured process, the program goes through four process steps: process initiation, program analysis, program development, evaluation of the process and results. A major challenge in this process is the role of program professionals. The goal is to establish them as change agents for a didactically-aligned study program. Outcome: Role of educational development After briefly introducing the two examples, the roles of program professionals and educational development in HEI will be discussed. The questions guiding the discussion will be: • How can program development be established as a continuing task, closely tied to quality development? • How can the competencies of program professionals be developed and the local capacity and ownership be strengthened? • How can educational development support program development and provide vital impulses? Audience Engagement. Depending on the number of participants, first the questions will be discussed in groups. To put the results of the discussion on record, it will be summarized and uploaded in our weblog for further discussion after the session.
Keywords: curriculum development; study programs; Bologna; educational development; higher education

Eine Systematisierung komplementärer Zugänge zur Lehrentwicklung am Beispiel des Förderprogramms Lehren - Jenert, Tobias
Das Förderprogramm Lehren, organisiert von der Alfred Toepfer Stiftung F.V.S., kombiniert und erprobt verschiedene Ansätze zur Entwicklung der Lehrqualität an Hochschulen. Der vorgeschlagene Beitrag charakterisiert die unterschiedlichen Zugänge, beschreibt der Potenziale und Grenzen und reflektiert Möglichkeiten, komplementäre Lehrentwicklungs-Ansätze zu kombinieren. Das "Lehren Jahresprogramm" bringt Lehrende, Hochschuldidaktiker/-innen und Leitungspersonen im Rahmen von fünf themenbezogenen Workshops zusammen. Der Austausch im Rahmen der Workshops soll die Teilnehmenden neben der individuellen Kompetenzentwicklung und gegenseitiger Perspektivübernahme dabei unterstützen, Innovationsprojekte an ihren Hochschulen zu entwickeln bzw. zu implementieren. Das Jahresprogramm vertritt damit einen Ansatz, der Lehrqualität durch die Gestaltung organisationaler Rahmenbedingungen an den Hochschulen zu entwickeln versucht. Mit der Kombination verschiedener Akteursgruppen sowie durch die zentrale Organisation des Programms soll eine Community von Lehrentwickler/-innen geschaffen werden, die Strategien zur lehrbezogenen Organisationsentwicklung an Hochschulen entwickelt und teilt. Demgegenüber setzt das "Lehren-Kolleg" auf einen fachdidaktischen Zugang zur Lehrentwicklung an Hochschulen. So befassen sich im aktuellen Durchgang Teams aus sieben Hochschulen mit der Gestaltung der Mathematikausbildung in den Ingenieurswissenschaften. Auch hier werden von den teilnehmenden Hochschulvertreter/-innen jeweils Innovationsprojekte bearbeitet, wobei diese stets auf die fachdidaktische Fragestellung des Kollegs ausgerichtet sind. In diesem Ansatz spiegelt sich die starke Bedeutung wissenschaftlicher Disziplinen an Hochschulen wider. Die disziplinäre Zugehörigkeit gilt als stärkstes Element der beruflichen Identität von Hochschullehrenden und schlägt sich dementsprechend in den Kulturen einzelner Studienfächer nieder. Der Beitrag stellt die beiden Zugänge zur Lehrentwicklung - organisations- und fachbezogen - vor dem Hintergrund erster Ergebnisse einer umfangreichen Begleitforschung dar. Dabei geht es nicht darum, die Ansätze konkurrierend darzustellen und sie hinsichtlich ihrer Effektivität zu vergleichen (i.S. der Debatte Fach- versus allgemeine Didaktik). Vielmehr werden die komplementären Potenziale und Schwächen herausgearbeitet, um schliesslich das Konzept eines kombinierten Ansatzes der Lehrentwicklung zu entwerfen, der eine möglichst umfangreiche Dissemination im Rahmen der komplexen Organisationsstrukturen von Hochschulen ermöglichen kann.
Keywords: Lehrentwicklung; educational development

On the assessment of attitudes towards the study process and the university: Attitudes towards the Study Environment Questionnaire (ASEQ) - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
The purpose of the research was to develop and validate an instrument for the assessment of attitudes towards the study environment in higher education contexts. The questionnaire is designed to measure students' attitudes towards two particular objects: the university (or Higher Education Institution) and the process of studying. Five studies at two different universities were conducted to develop and validate the Attitudes towards the Study Environment Questionnaire (ASEQ). In total, 1640 students filled in the questionnaire. Reliability tests and exploratory factor analysis as well as confirmatory factor analysis showed satisfactory psychometric characteristics of the ASEQ. Each part of the questionnaire is internally consistent and construct validity of the scales is supported by correlations with other constructs as assumed by current theories: Positive attitudinal constructs (normative behavior, autonomy, joy, self-efficacy, and task value) are positively related to intrinsic motivation and the expected study performance while anxiety is negatively related to these constructs. Since attitudes towards the study situation are connected to student engagement and motivation, the study contributes to the theory of student learning by providing a validated instrument to assess attitudes. Thus, the ASEQ can support further research on student performance and development by providing an instrument for the hitherto neglected but nonetheless extremely relevant domain of attitudes. Also, the questionnaire can be used as a diagnostic instrument for higher education faculty and administration to trace students' attitudinal development over time - a factor of prime importance for student socialization during the introductory phase of studying.
Keywords: attitudes; teaching and learning; studying; higher education institution; theory of planned behavior; instrument development

Reflection, abstraction and theorizing in design and development research - Gregor, Shirley; Müller, Oliver; Seidel, Stefan (European Conference on Information Systems)
Keywords: Abstraction; Affordances; Design Science Research; Design Theory; Information Systems Development; Reflection; Theorizing

The Effects of Negative Incidents in Sustainability Reporting on Investors’ Judgments–an Experimental Study of Third‐party Versus Self‐disclosure in the Realm of Sustainable Development - Reimsbach, Daniel; Hahn, Rüdiger (Business Strategy and the Environment)
ABSTRACT This study examines how the disclosure of negative sustainability‐related incidents affects the investment‐related judgments of decision‐makers. Participants in a sequential 2 × 2 between‐subjects experiment first received a company's financial information before viewing additional sustainability information (by the company and by a non‐governmental organization (NGO); with and without negative disclosure). Results indicate that self‐reporting of negative incidents does not affect decision‐makers’ stock price estimates and investment decisions compared with judgments based on financial information only. However, third‐party disclosure of these incidents by a NGO has a negative affect on these investment‐related judgments. Furthermore, the magnitude of the NGO reporting effect depends on whether the company itself simultaneously reports these incidents. Thus, disclosing negative incidents in sustainability reporting could lose some of its apparent stigma. Instead of avoiding negative reporting altogether, managers might use it as a risk mitigation tool in their reporting strategy. The results also emphasize the power of the often‐mentioned ‘watchdog’ function of NGOs acting as stakeholder advocates. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Studienprogramme als hochschuldidaktische Gestaltungs-und Untersuchungseinheit - Jenert, Tobias
In den vergangenen Jahren wurden viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren geäussert: Schlagworte wie Verschulung oder Entwissenschaftlichung sind zu hören und Studierende stehen im Verdacht, ihr Studium eher als Credit-Point-Jagd denn interessengeleitet zu gestalten (z.B. Stegemann, 2007, o. S.; Schultheis, et al. 2008). Meist handelt es sich jedoch um anekdotischen Beschreibungen, bis auf wenige Ausnahmen fehlen empirisch belegte Erkenntnisse.1 Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Vorwiegend wurde Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht (Aineley, 2008). Forschungsfokus. Die diesem Beitrag zugrunde liegende Studie nimmt diese Forschungslücke auf und untersucht Zielvorstellungen und Handlungsstrategien Studierender bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen. Im Einzelnen wird gefragt, (1) welche Vorstellungen und Wahrnehmungen das Handeln Studierender prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Als theoretischer Rahmen wurde die so genannte Kulturpsychologie herangezogen, die Handeln als Resultat einer Wechselwirkung von individuell-psychischen Merk-malen und sozio-kulturell vermittelten Vorstellungen versteht (Shweder, 1991; Bruner, 1990).
Keywords: Hochschulentwicklung; Studienprogramme; Curriculum Development; Higher Education; Faculty Development

" Nur" didaktisch oder auch strategisch?: Strukturelle Verankerung, Aufgaben-und Wirksamkeitswahrnehmungen hochschuldidaktischer Einrichtungen in Deutschland - Jenert, Tobias; Brahm, Taiga
Die Lehrpraxis an Hochschulen breitenwirksam und nachhaltig zu verbessern, gehört zu den schwierigsten Herausforderungen für die Hochschuldidaktik. Ein möglicher Weg besteht darin, als hochschuldidaktische Einrichtung stets mit Blick auf die Gesamtstrategie der Hochschule und Anspruchsgruppen in der Hochschulleitung und -administration zu agieren (Jenert & Brahm, 2010). Es stellt sich die Frage, welche Vorstellungen bezüglich der eigenen Aufgaben und der Wirksamkeit des eigenen Handels hochschuldidaktische Stellen in Deutschland haben. Mit einer Online-Befragung von Leitungspersonen im Bereich Hochschuldidaktik und -entwicklung in Deutschland konnten 35 Personen (72 angeschrieben) erreicht werden, wobei sich ein breiter Querschnitt verschiedener Einrichtungen ergab. Abgefragt wurden (1) Struktur und institutionelle Anbindung der Einrichtung, (2) Wahrnehmung der eigenen Wirksamkeit sowie (3) Aufgabenschwerpunkte und notwendige Kompetenzen. Die Ergebnisse zeigen, dass einerseits ein Bewusstsein für Herausforderungen jenseits didaktischer Aus- und Weiterbildung besteht und die strategische Dimension erkannt ist. Gleichzeitig zeigt die Betonung "traditioneller" Aufgaben und Kompetenzen, dass die strategische Dimension im Tagesgeschäft oft noch keine zentrale Rolle spielt.
Keywords: Hochschulentwicklung; higher education development; Hochschuldidaktik

Developing a learning centered model for designing and managing study programmes - Jenert, Tobias
Research on teaching and learning in higher education has first and foremost centered on individuals, i.e. students' and teachers' approaches to learning and teaching as well as methods (Entwistle, McCune, & Scheja, 2006; Entwistle & Peterson, 2004). As a consequence, concepts on how to improve and innovate education at higher education institutions (HEI) have stayed on the level of individual courses, trying to qualify teachers to implement new teaching and learning methods in their classrooms (Aineley, 2008, S. 619). Yet, there are both theoretical as well as practical reasons that argue for a broader perspective on learning processes and, as a consequence, reach beyond the course-level but focus on entire educational programmes instead: First, over the last thirty years or so, learning theories are increasingly stressing the importance of (a) social-material contexts (McInerney & van Etten, 2002) as well as (b) learners' subjective experiences. This suggests that a course of study be not regarded as a mere addition of more or less independent courses, but rather as a holistic learning experience. This includes the sum total of a student's educationally purposeful social-material interactions at a HEI both within and outside the classroom (cf. Hu & Kuh, 2002). A second, more practical reason why educational researchers and designers should take a closer look on the design of educational programmes lies in the Bologna process: The introduction of the European Credit Transfer System as well as the tow-tiered study structure force HEI to systematically craft their programmes' internal structure. Due to the fact that there are virtually no pedagogical concepts concerning the design of study programmes, these design processes have so far been dominated by administrative considerations, largely neglecting students' experiences within the programme structures (Winter, 2009; Hildbrand, Tremp, Jäger & Tückmantel, 2008). Thus, it can be concluded that there is a lack of knowledge on how distinctive design features of study programmes (1) are perceived by students and (2) impact on their action strategies concerning for example the selection of learning activities, the attribution of resources for learning, and social interactions with their peers.
Keywords: educational development; study programmes; approaches to studying

Learning culture as a prerequisite for an institution-wide approach to educational development - Brahm, Taiga; Gebhardt, Anja; Jenert, Tobias
Over the last two decades, the discussion about innovating teaching and learning at higher education institutions (HEI) has concentrated on various core concepts: such as an increased focus on learning outcomes as competencies and more student-centered teaching. These concepts form part of what Barr and Tagg (1995) have termed the "shift from teaching to learning". However, very few approaches have been proposed so far in the scholarly literature on how to actually transfer such normative concepts into the practice of teaching and learning at HEI. In order to sustainably develop the practices of teaching and learning at HEI, it is necessary to comprehend the prerequisites for educational development. The construct of "learning culture" can be seen as a possible concept to explicate these prerequisites. The aims of this study are to (a) propose an institution-wide approach to educational development at HEI and to (b) present a comprehensive instrument to diagnose learning culture as a starting point for educational development. The findings of the study include a first version of the Learning Culture Inventory for HEI. The students' version of the instrument encompasses 12 scales for the individual, 12 for the pedagogical interactions and 5 for the organizational dimension. The assumed basic factor structure of the instruments could be confirmed. With the institution-wide approach to educational development and the Learning Culture Inventory, this study can provide the basis for sustainable developmental initiatives to innovate teaching and learning at HEI.
Keywords: higher education; instrument development; strategy; educational development

Can state-of-the-art saliency systems model infant gazing behavior in tutoring situations? - Narayan, Vikram; Lohan, Katrin Solveig; Tscherepanow, Marko; Rohlfing, Katharina; Wrede, Britta (Frontiers in Computational Neuroscience)
The behavior for a humanoid robot is often modeled in accordance with human behavior. Current research suggests that analyzing infant behavior as a basis for designing the robot behavior can guide us to a natural robot interface. Based on this idea many researchers support saliency systems as a bottom-up inspired way to simulate infant-like gazing behavior. In the field of saliency systems many different approaches have proposed and quantified in terms of speed, quality and other technical issues. But so far, no one compared and quantified them in terms of natural infant tutor interaction. The question we would like to address in this paper is: Can state-of-the-art saliency systems model infant gazing behavior in tutoring situations? By addressing these issues we want to take a step towards an autonomous robot system, which could be used more natural interaction experiments in future.
Keywords: child gazing behavior; computer vision; saliency; development